2022
DOI: 10.1117/1.oe.61.9.095109
|View full text |Cite
|
Sign up to set email alerts
|

Optimized shape and structure of artificial bioparticles to enhance the optical extinction properties

Abstract: . A multilayer structure of microbial cells can result in multiple attenuations of electromagnetic waves, making the biological particles have a strong extinction ability. However, the influence of various morphologies on infrared band optical extinction performance of biomaterials is unclear. The combination of shape, dimension, and structure parameters is proposed to evaluate and enhance the optical extinction properties of artificial bioparticles. Combined with the preliminary work of our research group, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Zhao Xinying et al [23] studied the influence of the moisture content of the microbial material on its IR extinction performance from the aspects of composition and structure, obtained the qualitative rule between the moisture content and its absorption performance, and quantitatively calculated the relationship between the moisture content and its scattering characteristics. Ding Wanying et al [24] studied the relationship between the multilayer structure of microbial cells and extinction ability, and found that the chain-shaped particles with more constituent spheres and a bending angle of 60 deg as well as the ellipsoid-shaped particles with an axis ratio of 1:2 exhibit better extinction properties in the 3.0-5.0 μm and 8.0-14.0 μm wavebands. Huang Baokun et al [25] measured the dynamic change of the transmittance of 632.8nm laser in biological materials and found that when the biological material is stimulated by the laser, the stress response occurs, and the movement of escaping light is the main factor of causing the change of the transmittance.…”
Section: The Extinction Characteristics Of Monomer Particlesmentioning
confidence: 99%
“…Zhao Xinying et al [23] studied the influence of the moisture content of the microbial material on its IR extinction performance from the aspects of composition and structure, obtained the qualitative rule between the moisture content and its absorption performance, and quantitatively calculated the relationship between the moisture content and its scattering characteristics. Ding Wanying et al [24] studied the relationship between the multilayer structure of microbial cells and extinction ability, and found that the chain-shaped particles with more constituent spheres and a bending angle of 60 deg as well as the ellipsoid-shaped particles with an axis ratio of 1:2 exhibit better extinction properties in the 3.0-5.0 μm and 8.0-14.0 μm wavebands. Huang Baokun et al [25] measured the dynamic change of the transmittance of 632.8nm laser in biological materials and found that when the biological material is stimulated by the laser, the stress response occurs, and the movement of escaping light is the main factor of causing the change of the transmittance.…”
Section: The Extinction Characteristics Of Monomer Particlesmentioning
confidence: 99%
“…The extinction characteristics of biomaterials have been widely studied by theoretical calculation. The extinction efficiency factor of different-shaped biological particles was calculated [8,9] , and the extinction characteristics of the monodisperse [4,7,10,11] and polydisperse [12] biological particle aggregates have been explored. However, previous models for calculating the extinction characteristics of biomaterials used spherical particles for aggregation, without considering the aggregation of irregularly shaped particles, and without considering the numerical simulation of randomly oriented irregular particle aggregation.…”
Section: Introductionmentioning
confidence: 99%